Sei sulla pagina 1di 10

P 1 = (1, 0, 0), −−→

P 1 P 2

P 2 = (0, 2, 0),

P 3 = (2, 1, 2)

−−→ P 1 P 3

P 1 P 2

P 1 P 3

−−→ P 1 P 2 −−→ =

−−→

P 1 P 2 −−→

=

(0

1, 2 0, 0 0) = (1, 2, 0)

P 1 P 3 = (2 1, 1 0, 2 0) = (1, 1, 2)

−−→

P

−−→

P

1

P 2 ×

−−→

P 1

1

P 3

−−→ P 1 P 3

P 2 ×

= (4, 2, 3)

P 1 , P 2 P 3

−−→

P 1

d

d = (4.1 + 2.0 + (3).0) = 4

4x + 2y 3z 4 = 0

n =

−−→

P 1 P 3

P 1 P 2 ×

r : x = 1 + α, y = 2 + 2α, z = 3 + α,

s : x = 2β, y = 2 + 4β, z = 1 + 2β,

α R

β R

v r

v = (1, 2, 1) v α

w

s

β

v ×

w

= (2, 4, 2)

w

w

v

× w

= (0, 0, 0)

v

w

v × w = (0, 0, 0) v w w = 2 v w v

x, y z P α β

P = (x, y, z)

1 + α = 2β

2 + 2α = 2 + 4β

3 + α = 1 + 2β

2 + 2α = 4β

2 + 2α = 4β

+ 2α = 2 + 4β

2

r s

v w

P 0 r

P 0 = (1, 2, 3)

P 1 s

P 1 = (0, 2, 1)

P 0 r s

−−→

P 1

P 0

−−→ P 0 P 1

−−→ P 1 P 0

× w

−−→ P 1 P 0

dist(P 0 , s) = ||

× w ||

|| w ||

= (1 0, 2 2, 3 1) = (1, 0, 2)

−−→ P 1 P 0

× w = (8, 2, 4)

||

−−→ P 1 P 0

×

w || = (8) 2 + 2 2 + 4 2 = 64 + 4 + 16 = 84

w

||

w || = 2 2 + 4 2 + 2 2 = 4 + 16 + 4 = 24

−−→ P 1 P 0

dist(P 0 , s) = ||

× w ||

|| w ||

= 84

24

r s

r s r s

dist(r, s) = dist(P 0 , s) = 84

24

n

1

Ω : 2x + 3y + z = 0

Γ : x + y + 1 = 0

x, y z

n

1

= (2, 3, 1)

n

1

n

2

Γ

x, y z Γ

n

2

= (1, 1, 0)

n

2

n

1

× n 2

n

1

× n

2

n 1

n

2

= (1, 1, 1)

v

n

1

n

2

n

1

= (0, 0, 0)

w

× n

2

w v

Γ

n

1

n

2

n 1 2

n

θ →− n

cos θ =

n

1

1

n

2

n

2

n || |

||

1

n ||

2

n

1

n

2

→− n

1

n

2

= (2, 3, 1) (1, 1, 0) = 2.1 + 3.1 + 1.0 = 2 + 3 = 5

n

1

||

n || = 2 2 + 3 2 + 1 2 = 4 + 9 + 1 = 14

1

n 2

|| n || = 1 2 + 1 2 + 0 2 = 1 + 1 = 2

2

cos θ =

→− n

1

n

2

n || |

||

1

n || =

2

5

28

Γ

Γ

n

1 n

2

cos(Ω, Γ) = | cos θ| =

5

28

=

5

28

Γ

n

n n

n

1

2

1

2

A =

A

0

2

1

2

1

1

1

1

0

0

1

1

0

0

0

3

a 12 a 12 = 1 a 12 A

A 12 =

2

1

2

0

1

1

0

0

3

A 12 = (b ij ) 3×3 b 11 b 11 = 2 b 11 A 12

B 11 = 1 1

0

3

det(B 11 ) = 1.3 0.1 = 3

A 12

det(A 12 ) = b 11 ˜ b 11 = b 11 .(1) 1+1 det B 11 = 2.1.3 = 6

A

det(A) = a 12 a˜ 12 = a 12 .(1) 1+2 . det(A 12 ) = 6

0

A = 2

4

1

1

2

0

1

2

A

a 12 a 12 A

A 12 =

2

4

1

2

det(A 12 ) = 2.2 4.1 = 4 4 = 0

A

det(A) = a 12 a˜ 12 = a 12 .(1) 1+2 . det(A 12 ) = 0

det(A) = 0

y = 1 2x + y + z = 2


4x + 2y + 2z = 4

0

2

4

1

1

2

0

1

2

1

2

4

AX = B

1

1

2

0

A = 2

4

0

1

2

B =   2

1

4

A

0

2

4

1

1

2

0

1

2

1

2

4

0

2

0

1

1

0

0

1

0

1

2

0

2

0

0

1

1

0

1

0

0

2

1

0

2

0

0

0

1

0

1

0

0

1

1

0

1 1 2

1

0

0

0

1

0

1

2

0

0

1

2

1

0

0

1

0

1

0

0

1

2

0

0

1

2

1

0

x + 2 z = 1

1

2

y = 1

z = α R

 

x

y =

z

1

2

1

α

α

2

,

α R

0

A = 2

4

1

1

2

0

1

2

A

a 12 a 12 A

A 12 =

2

4

1

2

det(A 12 ) = 2.2 4.1 = 4 4 = 0

A

det(A) = a 12 a˜ 12 = a 12 .(1) 1+2 . det(A 12 ) = 0

det(A) = 0

y = 1 2x + y + z = 2


4x + 2y + 2z = 5

0

2

4

1

1

2

0

1

2

1

2

5

AX = B

1

1

2

0

A = 2

4

0

1

2

B =   2

1

5

A

0

2

4

1

1

2

0

1

2

1

2

5

0

2

0

1

1

0

0

1

0

1

2

1

2

0

0

1

1

0

1

0

0

2

1

1

2

0

0

0

1

0

1

0

0

1

1

1

1 1 2

1

0

0

0

1

0

1

2

0

0

1

2

1

1

0x + 0y + 0z = 1

2

A = 2

4

1

1

0

0

1

2

A

a 11 a 12 a 11 A

A 11 =

1

0

1

2

det(A 12 ) = 1.2 1.0 = 2

a 12 A

A 12 =

2

4

1

2

det(A 12 ) = 2.2 4.1 = 4 4 = 0

A

det(A) = a 11 a˜ 11 +a 12 a˜ 12 = a 11 (1) 1+1 det(A 11 )+a 12 (1) 1+2 det(A 12 ) = 2.1.2+1.(1).0 = 4

det(A)

= 0

2

2

4

1

1

0

0|1

1|0

2|0

0

1

0

0

0

1

2

2

4

1

1

0

1|0

0|1

2|0

1

0

0

0

0

1

2

0

4

1

0

0

1

  0

1

2

0

4

0

1|0

1|1

2|0

1|0

1| − 1

2|0

1

1

0

1

1

0

0

0

1

0

0

1

0

0

1

4

0

2

2|0

1| − 1

1|0

0

1

1

1

0

0

1

0

2

4

0

0

0

0

1

2|0

1| − 1

0|0

0

1

1

4

0

0

0

0

1

0|2

1| − 1

0|0

2

1

1

1

0

2

1 4 1

1

0

0

0

0

1

0| 1 1| − 1

0|0

2

1

1

1

2

1

4

0

2

1

0

0

0

1

0

1

0|

0|0

2

1| − 1

1

2

1

1

1

4

2

0

A

A 1 =

1

2

0

1

1

2

1

1

= 1

2x + y

2x + y + z2

  4x + 2z = 4

1

4

2

0

2

2

4

1

1

0

0

1

2

1

2

4

AX = B

2

A = 2

4

1

1

0

0

1 B =   2

2

1

4

A

X = A 1 B = 0

1

1 2

1

1

2

1

1

4

2

0

1

2 = 6

1

4

1

2